Residents’ willingness to become peer-to-peer tourism experience providers in mass tourism destinations. - Garau-Vadell, Joan B.; Orfila-Sintes, Francina; Rejón-Guardia, Francisco (Elsevier, 2023)
In this article we explore residents’ willingness to become peer-to-peer (P2P) tourism experience providers. Grounded in the theory of planned behaviour (TPB) and the self-determination theory (SDT), we put forward a model relating residents’ willingness and their attitude towards such experiences, their resources and capabilities, their perceptions of P2P tourism experiences and their intrinsic and extrinsic motivations. An empirical survey was conducted among 880 residents of Majorca (Spain), one of the top leading mass tourism destinations in Europe. The results indicate a direct and positive relationship between residents’ attitude towards P2P tourism experiences, their resources and capabilities, their intrinsic motivations (enjoyment and wellbeing gains), and their willingness to become P2P tourism experience providers. Enjoyment and wellbeing gains stand as the two most important influences of residents’ willingness. Surprisingly, the direct influence of extrinsic motivations, such as economic and reputational benefits, has not been proven. Furthermore, a negative indirect influence of the economic benefits on willingness was unveiled. The findings allow relevant managerial implications to be considered for the development of competitive and sustainable tourism destinations.
Keywords: Turismo - Modelos econométricos; Residents’ willingness to participate; Peer-to-peer providers; Theory of planned behaviour; Self-determination theory